Pengaruh Tingkat Kematangan Buah, serta Lama Fermentasi dan Penyangraian Biji terhadap Karakter Fisikokimia Kopi Robusta - Elsera Br Tarigan; Juniaty Towaha (Jurnal Tanaman Industri dan Penyegar, 2017)
Robusta coffee is the most widely cultivated coffee in Indonesia. However, flavor quality of coffee is low due to improper harvesting and postharvest handling by farmers. Flavor quality mostly determined by fruit maturity level, fermentation and roasting time. The research aimed to investigate the effect of fruit maturity level, fermentation and roasting time on the physico-chemical characteristics of Robusta coffee. The research was conducted at Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), from May to July 2017, used a completely ranndomized block design with 3 factors. The first factor was fruit maturity level (red and reddish yellow), second factor was bean fermentation (24 and 36 hours) and the third factor was roasting time (10 and 13 minutes). Physical quality covered percentage of live insects, moisture content, foreign materials and amount of defective beans. Chemical quality covered moisture content, ash, fat, protein, caffeine and acidity. The results showed that physical quality of fermented beans i.e. moisture content and amount of defective beans were affected by fruit maturity level and fermentation time, while foreign materials is affected by the interaction between these two factors. Chemical quality of coffee i.e. fat and caffeine content were affected by the interaction between fruit maturity level, and fermentation and roasting time. Water and protein content were affected by interaction between fruit maturity level and fermentation time, and interaction between fruit maturity level and roasting time. The ash content is affected by the roasting time, whereas pH is affected by fermentation time and roasting time.